What were they thinking? : unconventional wisdom about management - Pfeffer, Jeffrey. (Harvard Business School Press, 2007)
Every day companies and their leaders fail to capitalize on opportunities because they misunderstand the real sources of business success. Based on his popular column in "Business 2.0", Jeffrey Pfeffer delivers wise and timely business commentary that challenges conventional wisdom while providing data and insights to help companies make smarter decisions. The book contains a series of short chapters filled with examples, data, and insights that challenge questionable assumptions and much conventional management wisdom. Each chapter also provides guidelines about how to think more deeply and intelligently about critical management issues. Covering topics ranging form managing people to leadership to measurement and strategy, it's good organizational advice, delivered by Dr. Pfeffer himself.